Crime of Sexual Violence Against Children (Study at Kebumen Police Station) - Setiyawan, Deni; Noor Rahmad (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
In Indonesia, cases of sexual violence have increased every year, the victims are not only adults but now have spread to teenagers, children and even toddlers. The purpose of this research focuses on identifying and analysing the obstacles faced by investigators and the efforts made by investigators in revealing cases of sexual violence against children. This research uses empirical methods through interview data and field observations, then conceptually analysed to find obstacles and efforts of investigators in overcoming cases of sexual violence in children. The results of the study found that the main obstacle for investigators in uncovering criminal acts of sexual violence against children is the lack of information from children who experience sexual violence due to trauma. The absence of a psychologist in the investigating team, difficulties in bringing in a psychologist when a case of child abuse occurs. Efforts made by Kebumen Police investigators are to call a psychologist when there is a case of sexual violence against a child. Efforts to provide assistance by psychologists, and traumatic recovery for children who experience sexual violence. It is hoped that the Kebumen police will have a field of psychology experts who specialise in handling child sexual abuse crimes in Kebumen.